Reduced bone mineral content and normal serum osteocalcin in non-steroid-treated patients with juvenile rheumatoid arthritis. Issue 3 (March 1995) - Polito, C; Strano, C G; Rea, L; Alessio, M; Iammarrone, C S; Todisco, N; Marotta, A; Iaccarino, E; Pirozzi, M
Abstract : OBJECTIVES–To distinguish the effects of juvenile rheumatoid arthritis (JRA) on bone mineralisation from those possibly caused by steroid therapy. METHODS–Bone mineral status was evaluated in 20 children (five boys and 15 girls) with active JRA who never received steroids. Seven had oligoarticular, nine had polyarticular, and four had systemic JRA. Bone mineral content (BMC) was assessed by single beam photon absorptiometry and expressed as a Z score relative to normal values in healthy children. Serum calcium, phosphate, and alkaline phosphatase were measured by colorimetric methods. Whole parathyroid hormone was assayed by Immuno Radiometric Assay. Serum osteocalcin was measured by specific radioimmunoassay. Nutrient intake was assessed by a 24 hours dietary recall. BMC and nutrient intake were also assessed in an age and sex matched control group. RESULTS–BMC was -1.5 (SEM 0.8) Z scores in patients and 0.4 (0.3) in the control group (p = 0.02). BMC averaged -4.9 (2) Z scores in the systemic JRA group, -1 (0.6) in the polyarticular group and 0.3 (0.7) in oligoarticular JRA patients. Serum calcium, phosphate and osteocalcin values were normal in all patients. No significant difference was found between JRA patients and controls in calcium, phosphate, energy, and protein intake. CONCLUSION–JRA subjects have significantly reduced BMC even in the absence of any steroid therapy. Bone demineralisation appears to depend more on disease activity and on reduced motility than on reduced nutrient intake.